Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain Et Causa Spondylosis Di RSUD Soetomo Surabaya - Anggawinata, Zakki Mubarrok; , Totok BudiSantoso, S.Fis., M.PH (2016)
Background: Spondilosis lumbalis is a disease which attack low back as the effect of denegrative. Occurs of the presence of osteophytes at about intervertebra which caused a major complaint of pain in the waist. One of the modality which can use for this case is Ultrasound to decrease the pain and muscle spasm and William Flexion exercise to increase socket's movement range. Purpose: this paper has purpose to knowing whether Ultrasound and William Flexion exercise can decrease the pain, increase socket's movement range, increase MMT, decrease the spasm, and increase fungsional activity. Result: after done five times therapy on low back pain et causa Spondylosis patient, it was gotten data such as: decrease of pressure pain from T0:4,2 become T5:1,3 the pain of movement from T0:7,8 cm become T0:3,6. Increase socket's movement range in fleksor movement from T0: 5 cm become T5:7 cm, ekstensor movement from T0: 2 cm become T5:3 cm lateral ekstensidekstra movement from T0:7 cm there is no different on T5:7 cm, lateral fleksisinistra movement from T0:7 cm there is no difference on T5:7 cm. The increase of flekstor trunk muscle strenght T0: 3 become T5: 4, there is no increasing on ekstensor trunk muscle strenght T0:3 and T5:3. The decrease happened on Merectorspinae spasm T0:(+) become T5:(-). The increase of functional activity with result T0:17 become T5:12. Conclusion: Ultrasound and William Felxicon exercise can decrease the pain, increase socket;s movement range, increase muscle strenght, decrease spasm, increase functional activities.